Governance for development in Africa : solving collective action problems - Booth, David, 1945- (Zed Books, 2013)
Drawing on in-depth empirical research spanning a number of countries in Africa, this path-breaking book controversially argues that externally imposed good-governance approaches make unrealistic assumptions about the choices leaders are able to make, while ignoring the potential for addressing causes rather than symptoms. It offers a comprehensive, critical examination of the institutional barriers to economic and social progress in Africa and makes a compelling plea for fresh policy thinking.